Reaching Unbankable Segments Using Branchless Banking Model with Mosque Partnership: Study from Indonesia - Siswantoro, Siswantoro (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
Islamic banking has a market share that tends to be low compared to conventional banking. To overcome this problem, the government has issued a regulation regarding branchless banking, one of which is to expand access to banking services for the public. However, the implementation of branchless banking in sharia banking tends to be less than optimal. Due to the limited number of branch offices, it does not reach the lower-class segment of society and MSMEs (unbankable segment). This research offers an idea to solve this problem by designing a model framework for implementing branchless banking in Islamic banking through mosque partnerships. The method used is qualitative. The data sources used are of the secondary type in the form of journal articles, books, reports from the government, national news websites, and other relevant sources that have previously been accessed and downloaded. The data analysis technique uses descriptive analysis. The results show that the branchless banking framework model through mosque partnerships can be an alternative solution in targeting the unbankable market share so that it has the potential to increase market share in Islamic banks. It is supported by mosques' tremendous physical and non-physical potential in Indonesia. Nevertheless, the government is advised to make regulations regarding this matter immediately. In addition, Islamic banking is expected to maximize the role of investors and Islamic philanthropy such as waqf and allocate CSR funds or profits to support the necessary funds and optimize the mentoring process for mosque administrators.